The Simulation of Vortex Modes in Twisted Few-Mode Fiber With Inverse-Parabolic Index Profile - Zhiming Zhang; Xiuying Liu; Wei Wei; Lei Ding; Liqing Tang; Yigang Li (IEEE Photonics Journal)
The eigenmodes of an inverse-parabolic graded index fiber under torsion were investigated by using the finite element method simulation. These eigenstates correspond to orbital angular momentum modes except for the two polarized-vortex modes. The design of appropriate core parameters can lead to the difference in the effective refractive indexes between all adjacent modes being greater than 10−4 over a bandwidth of 1.5 to 1.6 μm, which is expected to be an ideal method for the generation of multiple vortex modes in few-mode fiber for optical communication. The results showed that the separation of these modes changes with twist rate. Compared to the twisted air-hole ring-core fiber, the optimal twist rate of this fiber was found to be an order of magnitude smaller, which provides a more feasible scheme for the combination of mode division multiplexing and wavelength division multiplexing. We speculate that this study may have promising prospects in various applications such as particle manipulation, imaging, and quantum communication.